A multi-level slow intelligence system for visualizing personal health care. (October 2017) - Chang, Shi-Kuo; Chen, JunHui; Gao, Wei; Lou, ManSi; Yin, XiYao; Zhang, Qui; Zhao, ZiHao
Abstract: This paper describes the design of an experimental multi-level slow intelligence system for visualizing personal health care, called the TDR system, consisting of interacting super-components each with different computation cycles specified by an abstract machine model. The TDR system has three major super-components: Tian (Heaven), Di (Earth) and Ren (Human), which are the essential ingredients of a human-centric psycho-physical system following the Chinese philosophy. Each super-component further consists of interacting components supported by an SIS server. This experimental TDR system provides a platform for exploring, visualizing and integrating different applications in personal health care, emergency management and social networking.